Measurement of Maximum Value of Dental Radiograph to Predict the Bone Mineral Density - Sri Lestari; Mohammad Diqi; Rini Widyaningrum (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Post-menopausal woman has a high risk to have osteoporosis. The condition of osteoporosis is characterized by the bone mineral density. The gold standard of BMD examination is using DEXA scan, but it has a problem in high cost and limited availability. So the study about the alternative to overcome the problem is necessary. The objective of this study is to measure the maximum value of periapical radiograph and determine its ability to be a predictor for bone mineral density of lumbar spine and hip.Image processing method was applied to 37 data subject that involved periapical radiograph and DEXA scan. The grayscale image was converted into binary image to observe the connectivity of the pixels. Measurement of maximum value for each radiograph has been done and continued by linier regression method between the maximum value with the BMD of lumbar spine and hip.The result of this study showed that the maximum value has a weak correlation with the BMD of lumbar spine and hip. The maximum value also cannot be the predictor for BMD of lumbar spine and hip as the significant of F is larger than 0,05 in the linier regression test.